The Enhancing of Nurses’ and Midwives’ Competence in Providing Spiritual Care through Innovative Education and Compassionate Care using the Spiritual Care Competency Self-Assessment Tool: Turkish Version - Karabey, Tuba (Journal of religion and health, 2025)
Spiritual care is an important part of holistic care and is at the center of nursing/midwifery care. Nurses/midwives are expected to graduate by receiving adequate training in spiritual care and gaining spiritual care competence during their student days. It is important to evaluate the spiritual care competencies of nursing/midwifery students and to correct the deficiencies, if any. Therefore, a self-assessment tool is needed to increase awareness and knowledge and improve skills and attitudes in the field of spirituality and pastoral care. One of these tools is EPICC (Enhancing Nurses’ and Midwives’ Competence in Providing Spiritual Care through Innovative Education and Compassionate Care). This EPICC Spiritual Care Education Standard describes the spiritual care competencies expected from undergraduate nursing and midwifery students. For every competence, the learning outcomes are described in aspects of knowledge, skills, and attitudes. This research was conducted with a methodological design to ensure that the Turkish version of the EPICC Spiritual Care Competency Self-Assessment Tool can be used as a reliable and valid measurement tool in nursing research in Turkey. Methodological and cross-sectional research design was used in the research method. The research was carried out with 300 nursing and midwifery students in Turkey. Data were collected using the personal information form and the EPICC Spiritual Care Competency Self-Assessment Tool. The results of exploratory factor analysis and confirmatory factor analysis confirmed the four-factor structure of the scale. Cronbach’s α, item-total correlation, test-retest analysis, and equivalent form analysis showed high reliability. EPICC Spiritual Care Competency Self-Assessment Tool For Student Nurses And Midwives: Turkish Validity And Reliability Study consists of 24 items on a five-point Likert-type scale. The Turkish version of the EPICC Spiritual Care Competency Self-Assessment Tool is a valid and reliable tool for assessing the Spiritual Care Competencies of nursing and midwifery students. Evaluating the Spiritual Care Competencies of nursing and midwifery students is an important issue, it is now possible in Turkey with this scale given its validity and reliability.